Effect of high hydrostatic pressure treatment and vine-shoot chips on the volatile fraction and sensorial profile of Chardonnay wines - Noviello, Mirella; Moreno, David; Martins, Nuno; Paradiso, Vito; Caponio, Francesco; Cabrita, Maria Joao; Valdés, Esperanza (IVES OenoOne, 2025)
This study evaluates the impact of toasted vine-shoot chips and high hydrostatic pressure (HHP), applied either separately or in combination, on the volatile composition and sensory properties of Chardonnay wines to investigate their individual and synergistic effects on wine quality. Five treatments were carried out: (i) untreated wine as a control (W), (ii) wine macerated for 35 days with vine-shoot chips (12 g L–1) (WCM), (iii) wine treated with HHP at 600 MPa for 30 minutes (WP), (iv) wine treated with HHP in the presence of vine-shoot chips, which were removed immediately after pressurization (WPC), and (v) wine treated with HHP and subsequently macerated for 35 days with vine-shoot chips (WPCM). Results show that maceration with vine-shoot chips (WCM) had a limited effect on volatile composition but increased astringency and structure. HHP application significantly altered the aromatic profile, increasing oxidation-related compounds, leading to sensory attributes such as bitterness and acidity. In contrast, the combined treatment of WPC and WPCM promoted the development of aged, woody, and balsamic notes associated with higher levels of acetates, alcohols, aldehydes, and ketones, without the negative oxidative effects observed in HHP-only wines. These findings indicate a synergistic effect between vine-shoot chip maceration and HHP, offering a promising strategy for accelerating wine ageing while preserving sensory quality. Optimizing processing parameters is critical in tailoring outcomes for specific varietals and desired wine styles.
Keywords: white wine; volatile compounds; sensorial analysis; wood